Radiometric method for the rapid detection of Leptospira organisms. - Manca, N (1986)
A rapid and sensitive radiometric method for detection of Leptospira interrogans serovar pomona and Leptospira interrogans serovar copenhageni is described. Stuart's medium and Middlebrook TB (12A) medium supplemented with bovine serum albumin, catalase, and casein hydrolysate and labeled with 14C-fatty acids were used. The radioactivity was measured in a BACTEC 460 (Johnston Laboratories). With this system, Leptospira organisms were detected in human blood in 2 to 5 days, a notably shorter time period than that required for the majority of detection techniques.